Exploring the Employment Status of Urban Street Children in Cumilla City, Bangladesh - Das, Rajib Chnadra; Hossen, Md Imran; Das, Roney Chandra (ARRUS Journal of Social Sciences and Humanities, 2025)
Employment plays a crucial role in human development, yet street children remain a significant challenge in many developing countries, such as Bangladesh. This study employs both qualitative and quantitative research methods, focusing on a primary survey conducted in specific districts of Bangladesh. The prevalent causes of children becoming street-dwelling are rooted in poverty, illiteracy, disease, and social injustice. The study specifically targets children who sleep on the streets, railway stations, bus stops, parks, religious sites, construction sites, cemeteries, and other large public areas. The main objective of this research is to explore the nature of labor among street children. Vulnerable children, particularly those who reside in public spaces, are the focal point of this study. A purposive sample of 20 children was selected from various areas in Comilla City for the survey. The findings reveal that the quality of life for these children is severely impacted by their lack of access to informal employment opportunities. The results indicate that homeless children endure precarious living conditions due to their involvement in the low-wage informal sector, leading to a cycle of poverty and vulnerability.